2021
DOI: 10.1039/d0na00941e
|View full text |Cite
|
Sign up to set email alerts
|

Folding and self-assembly of short intrinsically disordered peptides and protein regions

Abstract: Proteins and peptide fragments are highly relevant building blocks in self-assembly for nanostructures with plenty of applications. Intrinsically disordered proteins (IDPs) and protein regions (IDRs) are defined by the absence...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 179 publications
(228 reference statements)
0
12
0
Order By: Relevance
“…68 Others suggested that it was unclear whether the β-sheets in amyloid structures are antiparallel or parallel. 10,69 Also, it was discussed whether the low-frequency component around 1697 cm −1 , usually assigned to antiparallel β-sheets, was due to residues of nonfibrillar material. 56 In spider silk systems, the antiparallel character of the β-sheets was confirmed previously.…”
Section: = = °90mentioning
confidence: 99%
See 2 more Smart Citations
“…68 Others suggested that it was unclear whether the β-sheets in amyloid structures are antiparallel or parallel. 10,69 Also, it was discussed whether the low-frequency component around 1697 cm −1 , usually assigned to antiparallel β-sheets, was due to residues of nonfibrillar material. 56 In spider silk systems, the antiparallel character of the β-sheets was confirmed previously.…”
Section: = = °90mentioning
confidence: 99%
“…3 Further, due to their biodegradability, their high tunability, and their ability to form various nanostructures, IDPs are of great interest as synthetic polymer substitutes, 4 scaffolds for tissue regeneration 5 or nanodrugs. 6 On the other hand, intrinsically disordered structures can assemble into well-defined structures, which can be beneficial for an organism, i.e., the gain of function such as in pili of bacteria. 7,8 The assembly can also be disadvantageous, such as in so-called conformational diseases, where it leads to a loss of function like Amyotrophic Lateral Sclerosis, Huntington's disease, or Parkinson's disease to name just a few examples.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, α-helical structures, the most common secondary structures of natural proteins, are less exploited for the creation of assembled structures. Short peptides containing unmodified amino acids present weak intrinsic helical stability, which hinders their use to generate self-assembled helical structures [ 51 ]. One of the main strategies involves the use of helix-promoting noncoded amino acids such as β–amino acids and α-aminoisobutyric acid [ 52 ].…”
Section: Self-assembly Processmentioning
confidence: 99%
“…Considering these controversial findings about secondary structure supporting peptide fibrillization, a more easily accepted theory has risen that non-β-strand peptides could undergo fibrillization, accompanying which the conformation of peptide monomers also transformed to β-strand. Following the textbook theory that the secondary structure determines the tertiary structure, it seems to be reasonable to presume that disordered peptide monomers should transform to β-strand conformation before they can self-assemble into nanofibers. However, for these intrinsically disordered peptides, very few research studies have been systematically carried out to clarify the causal link between peptide fibrillization and β-strand conformation, i.e., which one comes first.…”
Section: Introductionmentioning
confidence: 99%